Implementasi Jurnalistik Profetik dalam Media Massa: Upaya Mewujudkan Keadilan dan Kebenaran di Tengah Tantangan Politik dan Ekonomi: Implementation of Prophetic Journalism in Mass Media: Efforts to Realize Justice and Truth in the Midst of Political and Economic Challenges - Ridwan, Ridwan; Arham Selo (DIRASAH: Jurnal Kajian Islam, 2025)
This study aims to identify the principles of prophetic journalism that can be applied in mass media practices, analyze the challenges journalists face in implementing this approach, and explore strategies and practical solutions to support its application. The research employs a qualitative approach with a descriptive-analytical method. The findings reveal that prophetic journalism offers an approach that integrates the values of justice, truth, and humanity in news reporting, positioning mass media as a moral guardian of society and a positive agent of social change. However, implementing these principles faces challenges such as political and economic pressures, ethical dilemmas, and conflicts between idealism and commercial demands. Nevertheless, strategies such as strengthening ethical commitments, gaining public support, and developing media business models that ensure editorial independence can help overcome these obstacles. The study recommends developing internal mechanisms within media organizations to ensure the application of prophetic journalism principles, enhancing journalists' competencies through continuous training, and fostering active public participation in supporting media with integrity. Further research on the impact of implementing prophetic journalism is also suggested to strengthen the theoretical and practical foundation of this approach. Thus, prophetic journalism holds significant potential to contribute to the creation of a more just, civilized, and moral society.